The determinants of unemployment rate in Malaysia - Ramli, Rafiqah (2014)
Unemployment is an important issue to all countries in developing economies. High unemployment means the labors resources are not being used efficiently. In macroeconomic framework, there are several factors that can affect the unemployment rate, such as population, inflation, the real growth output and etc. Therefore, this paper attempts to examine the linkages between the gross domestic product, inflation rate, and population with unemployment rate in Malaysia. For this study will use the time series annual data analysis covered from 1982 - 2012. The empirical evidences shows that there is a positive coefficient between the independence variables like real growth output, inflation, and population on unemployment rate in Malaysia.